Strategic management: A literature review and future research orientations - Tran, Dang Khoa (Edelweiss Applied Science and Technology, 2025)
The study was conducted to provide readers with a comprehensive understanding of the formation and evolution of strategic management studies, thereby proposing future research directions in this field. Bibliometric analysis was employed, with 29,771 documents downloaded from the Web of Science database. Techniques such as performance analysis, co-citation, co-occurrence, and keyword scatter plots were utilized using VOSviewer and Power BI software. The research findings indicate that strategic management research is founded on seven core principles, and eight research directions have been developed within the field. The study recommends that future research in strategic management should focus on developing countries, industries beyond business economics and science and technology fields, and Small and Medium-sized Enterprises (SMEs). Additionally, research topics that explore factors demonstrating strategic flexibility in turbulent environments—such as innovation, knowledge, technology, learning ability, and absorptive capacity—require further attention. The moderating effects of contextual factors are particularly emphasized as important areas for future investigation. Furthermore, the study offers an overview of strategic management to help managers gain a deeper understanding and apply these insights effectively in today’s dynamic context.